Riociguat for the Treatment of Chronic Thromboembolic Pulmonary Hypertension - Ghofrani, Hossein-Ardeschir; D'Armini, Andrea M; Grimminger, Friedrich; Hoeper, Marius M; Jansa, Pavel; Kim, Nick H; Mayer, Eckhard; Simonneau, Gerald; Wilkins, Martin R; Fritsch, Arno; Neuser, Dieter; Weimann, Gerrit; et al. (The New England journal of medicine, 2013)
In this trial, 261 patients with chronic thromboembolic pulmonary hypertension were assigned to placebo or to the soluble guanylate cyclase stimulator riociguat. At 16 weeks, riociguat had significantly improved the 6-minute walk distance and pulmonary vascular resistance. Chronic thromboembolic pulmonary hypertension is characterized by obstruction of the pulmonary vasculature by residual organized thrombi, 1 leading to increased pulmonary vascular resistance, progressive pulmonary hypertension, and right ventricular failure. 2 , 3 Patients with chronic thromboembolic pulmonary hypertension have a poor prognosis unless they receive treatment early. 4 Pulmonary endarterectomy is the standard treatment for chronic thromboembolic pulmonary hypertension and is the only potentially curative treatment. 5 However, surgery is not an option for all patients; some patients are ineligible for surgery owing to the occlusion of distal vessels or coexisting conditions, some decline surgery, and some do not have access to expert surgical . . .